Ensuring Comprehensive Care: An Audit on Physical Parameter Monitoring in Children and Adolescents With ADHD on Medication - Rakesh Sharma (BJPsych Open, 2025)
Aims: In child and adolescent psychiatry, particularly within Child and Adolescent Mental Health Services (CAMHS), monitoring the physical health of patients on ADHD medications is of paramount importance. Medications such as stimulants can have significant impacts on physiological processes, including cardiovascular health. This audit aims to assess current practices in monitoring physical parameters in children and adolescents prescribed ADHD medication at St Ann’s Hospital (Haringey), identify gaps in practice, and recommend improvements based on recent research.